Building a total quality culture - Batten, Joe (California : Crisp Publication, Inc., 1992)
This book presents an approach that systematically designs and builds a culture in which a total emphasis on quality reaches and affects all policies, practices, processes and people.
The path to the future -- The new leaders -- Making quality possibilities come true -- Peak performance at all levels -- Winners can be grown -- Tomorrow's culture
Includes bibliographical references.
Keywords: INDUSTRIAL MANAGEMENT